Characterization of Biodiesel by Unconventional Methods: Photothermal Techniques - Castro, Maria; Machado, Francisco; Rocha, Aline; Perez, Victor; Guimarães, André; Sthel, Marcelo; Corrêa, Edson; Vargas, Helion (IntechOpen, 2011)
None